Кримські готи в світлі історико-археологічних та етнологічних досліджень - Піоро, І.С. (Археологія, 2000)
На підставі вивчення старожитностей Південного та Південно-Західного Криму і матеріалів із могильників Центральної та Південно-Східної Європи, підтверджуються та конкретизуються дані писемних джерел про проникнення та тривале перебування готів на півострові. Використання широкого кола різноманітних джерел, минулих та сучасних етнологічних досліджень дозволяє відтворити історію кримських готів та їх нащадків до нового часу. О продвижении на юг различных германских племен свидетельствуют древние авторы (Аммиан Марцеллин, Зосим, Иордан, Агафий, Стефан Византийский Зонара и др.). Археологическим отражением расселения разноэтничных племен готского союза в Северном Причерноморье являются биритуальные могильники Черняховской культуры, в которых выделяются германские трупосожжения и сармато-аланские трупоположения. В Крыму такие могильники открыты в округе Херсонеса: совхоз «Севастопольский», Чернореченский, Бельбек I и другие. Кроме этого, во многих синхронных сармато-аланских могильниках, которые обнаружены на территории от дельты Дуная до низовьев Дона, включая Крым, в погребальном инвентаре присутствуют предметы Черняховской культуры, указывающие на направление проникновения населения. Могильники с германскими трупосожжениями типа Ай-Тодор открыты на южном берегу Крыма.
В период раннего средневековья в могильниках горного и южнобережного Крыма доминируют сармато-аланские погребальные традиции на основе обряда трупоположения. Однако в деталях женского парадного костюма из погребений в могильниках VI—VII вв. присутствуют типично готские этнографические черты.
Сообщение о готской области Дори, укрепленной «длинными стенами» при императоре Юстиниане I, содержится в труде Прокопия Кесарийского. Остатки «длинных стен» обнаружены в балке Каралез к северу от Мангупа (Дори-Дороса). С южной стороны «длинных стен» открыты поселение и могильник VI—X вв., принадлежавшие готам-федератам. Могильники готов-федератов открыты также на склонах Мангупа.
Сведения о германском языке крымских готов содержатся в трудах авторов XIII—XVI вв. (Рубрук, Барбаро, Бусбек). Таким образом, концепция крымских готов основывается на данных различных групп источников. The ancient authors (Ammiamis Marcellinus, Zosimus, Iordanes, Agathias, Stephanus Byzantius, Zonaras and others) testify to the advancement to the South of various Germanic tribes. The biritual burial-graunds of the Cherniakhovska culture in northern Black Sea coast are the archaeological reflection of the different ethnic Gothic Union. Germanic cremations, Sarmatiane and Alaniane graves become localized in the burial-grounds together. Such cemeteries (the state farm «Sevastopolic», the Black River, the Belbek I and others) were opened in the Crimea not far from Chersonesos. Besides that, the things of the Cherniakhovs’ka culture as the indication on the direction of the penetration of the population were found out in the graves of Sarmatian and Alaniane burial-grounds in the territory from the delta of the Danube to the Lower Don, including the Crimea. The cemeteries wits the Germanic cremations type Ai-Todor were opened in the south coast of the Crimea.
The Alaniane traditions dominated in the burial-grounds in the Crimean mountains and South coast during early Middle Ages. However, the typical Gothic etnographical traits in the details of female costumes were opened in the graves in many cemeteries of the 6th — 7th centuries.
The message about the Gothic region Dori which was fortified with the «long walls» by the emperor Ustinian is contaned in the work of Procopius Caesariensis. The rests of the «long walls» were found out in Karalez ravine to the north from Mangup (Dory-Doros) wich was the politycal centre of the Gothic region.
The settlement and the burial-ground of the period from the 6th to the 10th centuries which belonged to the Goths-Federats were opened near the «long walls». The burial-grounds of the Goths-Federats were opened in the slopes of Mangup too.
The information about Germanic language of the Crimean Goths is contained in the works of the authors of the 13th — 16th centuries (Rubruck, Barbara, Busbeck). So, the conception of the Crimean Goths is based on the facts of the various groups of the sources.